FIGURE 1 in Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae) - Fanciulli, Pietro Paolo; Leo, Chiara; Convey, Peter; Frati, Francesco; Carapelli, Antonio (Zenodo, 2018)
FIGURE 1. Folsomotoma octooculata: A, Dorsal chaetotaXy;, Ventral chaetotaXy of the head; C, Labium; Lp–Labial palp; Bmf–Basomedian field (submentum); Blf–Basolateral field (mentum); D, Ventral tube; E, Manubrium anterior VieW shoWing 3+3 spine–like setae, F, Ant. I lateral sensilla; G, Ant. Organ III; H, ChaetotaXy of tibiotarsus III; I, ChaetotaXy of the furca; K, Female genital opening; L, Male genital opening. Scale bars: 200 µm (A), 100 µm (B, I), 50 µm (D, K, L), 25 µm (C, E–H). : Published as part of Fanciulli, Pietro Paolo, Leo, Chiara, Convey, Peter, Frati, Francesco & Carapelli, Antonio, 2018, Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae), pp. 392-400 in Zootaxa 4392 (2) on page 395, DOI: 10.11646/zootaxa.4392.2.11, http://zenodo.org/record/1195334